2016
DOI: 10.1016/j.celrep.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

PIAS1 Promotes Lymphomagenesis through MYC Upregulation

Abstract: Summary The MYC proto-oncogene is a transcription factor implicated in a broad range of cancers. MYC is regulated by several post-translational modifications including SUMOylation, but the functional impact of this post-translational modification is still unclear. Here we report that the SUMO E3 ligase PIAS1 SUMOylates MYC. We demonstrate that PIAS1 promotes, in a SUMOylation-dependent manner, MYC phosphorylation at serine 62 and dephosphorylation at threonine 58. These events reduce the MYC turnover leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…SUMOylation not only prolongs MYC half-life preventing its proteasomal degradation, but also positively regulates MYC transcriptional activity. Significantly, we also demonstrated that MYC is SUMOylated in primary B-cell lymphomas (43). Furthermore, PIAS1-mediated SUMOylation is required to maintain the oncogenic activity of MYC in lymphoma cells.…”
Section: Pias1 Myc and Lymphomagenesissupporting
confidence: 61%
See 4 more Smart Citations
“…SUMOylation not only prolongs MYC half-life preventing its proteasomal degradation, but also positively regulates MYC transcriptional activity. Significantly, we also demonstrated that MYC is SUMOylated in primary B-cell lymphomas (43). Furthermore, PIAS1-mediated SUMOylation is required to maintain the oncogenic activity of MYC in lymphoma cells.…”
Section: Pias1 Myc and Lymphomagenesissupporting
confidence: 61%
“…Recently, PIAS1 has been reported to account for MYC SUMOylation (43,44) (Fig.2D). K51/52 are the major MYC SUMOylation sites.…”
Section: Pias1 Myc and Lymphomagenesismentioning
confidence: 89%
See 3 more Smart Citations